Feasibility of producing a short, high energy s‐band linear accelerator using a klystron power source. Issue 4 (20th March 2013) - Baillie, Devin; Aubin, J. St.; Fallone, B. G.; Steciw, S.
Abstract : Purpose: : To use a finite‐element method (FEM) model to study the feasibility of producing a short s‐band (2.9985 GHz) waveguide capable of producing x‐rays energies up to 10 MV, for applications in a linac‐MR, as well as conventional radiotherapy. Methods: : An existing waveguide FEM model developed by the authors' group is used to simulate replacing the magnetron power source with a klystron. Peak fields within the waveguide are compared with a published experimental threshold for electric breakdown. The RF fields in the first accelerating cavity are scaled, approximating the effect of modifications to the first coupling cavity. Electron trajectories are calculated within the RF fields, and the energy spectrum, beam current, and focal spot of the electron beam are analyzed. One electron spectrum is selected for Monte Carlo simulations and the resulting PDD compared to measurement. Results: : When the first cavity fields are scaled by a factor of 0.475, the peak magnitude of the electric fields within the waveguide are calculated to be 223.1 MV/m, 29% lower than the published threshold for breakdown at this operating frequency. Maximum electron energy increased from 6.2 to 10.4 MeV, and beam current increased from 134 to 170 mA. The focal spot FWHM is decreased slightly from 0.07 to 0.05 mm, and the width of the energy spectrum increased slightly from 0.44 to 0.70 MeV. Monte Carlo results show dmax is at 2.15 cm for a 10 × 10 cm 2 field, compared with 2.3 cm for a Varian 10 MV linac, while the penumbral widths are 4.8 and 5.6 mm, respectively. Conclusions: : The authors' simulation results show that a short, high‐energy, s‐band accelerator is feasible and electric breakdown is not expected to interfere with operation at these field strengths. With minor modifications to the first coupling cavity, all electron beam parameters are improved.